Risk, Predictors, and Outcomes of Acute Kidney Injury in Patients Admitted to Intensive Care Units in Egypt. Issue 1 (December 2017) - Abd ElHafeez, Samar; Tripepi, Giovanni; Quinn, Robert; Naga, Yasmine; Abdelmonem, Sherif; AbdelHady, Mohamed; Liu, Ping; James, Matthew; Zoccali, Carmine; Ravani, Pietro
Abstract Epidemiology of acute kidney injury (AKI) in developing countries is under-studied. We evaluated the risk and prognosis of AKI in patients admitted to intensive care units (ICUs) in Egypt. We recruited consecutive adults admitted to ICUs in Alexandria Teaching Hospitals over six months. We used the KDIGO criteria for AKI. We followed participants until the earliest of ICU discharge, death, day 30 from entry or study end. Of the 532 participants (median age 45 (Interquartile range [IQR]: 30–62) years, 41.7% male, 23.7% diabetics), 39.6% had AKI at ICU admission and 37.4% developed AKI after 24 hours of ICU admission. Previous need of diuretics, sepsis and low education were associated with AKI at ICU admission; APACHE II score independently predicted AKI after ICU admission. A total of 120 (22.6%) patients died during 30-day follow-up. Compared to patients who remained AKI-free, mortality was significantly higher in patients who had AKI at study entry (Hazard Ratio [HR] 2.14; 95% Confidence Interval [CI] 1.02–4.48) or developed AKI in ICU (HR 2.74; 95% CI 1.45–5.17). The risk of AKI is high in critically ill people and predicts poor outcomes. Further studies are needed to estimate the burden of AKI among patients before ICU admission.